The neutrophil-to-lymphocyte-ratio as diagnostic and prognostic tool in sepsis and septic shock - Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Forner, Jan; Dulatahu, Floriana; Brück, Lea Marie; Dudda, Jonas; Hoffmann, Ursula; Abba, Mohammed L.; Kittel, Maximilian; Bertsch, Thomas; et al. (Clinical laboratory, 2023)
Background: Studies investigating the diagnostic and prognostic value of the neutrophil-to-lymphocyte ratio (NLR) in sepsis or septic shock commonly included preselected subgroups of patients or were published prior to the current sepsis-3 criteria. Therefore, this study investigates the diagnostic and prognostic impact of the NLR in patients with sepsis and septic shock. Methods: Consecutive patients with sepsis and septic shock from 2019 to 2021 from the prospective "MARSS-registry" were included monocentrically. First, the diagnostic value of the NLR compared to established sepsis scores was tested for septic shock compared to sepsis. Second, the diagnostic value of the NLR with regard to positive blood cultures was tested. Thereafter, the prognostic value of the NLR was tested for 30-day all-cause mortality. Statistical analyses included univariable t-tests, Spearman ' s correlations, C-statistics, Kaplan-Meier analyses, Cox proportional regression analyses as well as uni-and multivariate logistic regression models. Results: A total of 104 patients were included, of which 60% were admitted with sepsis and 40% with septic shock. The overall rate of all-cause mortality at 30 days was 56%. With an area under the curve (AUC) of 0.492, the NLR was shown to have a poor diagnostic value with regard to the diagnosis of septic shock compared to sepsis. However, the NLR was shown to be a reliable parameter to discriminate between patients with negative and positive blood cultures when admitted with septic shock (AUC = 0.714). This was still evident after multivariable adjustment (OR = 1.025; 95% CI 1.000 -1.050; p = 0.048). In contrast, the NLR revealed a poor prognostic accuracy (AUC = 0.507) with regard to 30-day all-cause mortality. Finally, a higher NLR was not associated with an increased risk of 30-day all-cause mortality (log rank p-value = 0.775). Conclusions: The NLR was a reliable diagnostic tool for the identification of patients with blood culture confirmed sepsis. Yet, the NLR was not a reliable parameter to discriminate between patients with sepsis and septic shock nor between 30-day survivors and non-survivors.
Gesehen am 09.08.2023